Numerical Simulation of a One-Dimentional Non-Linear Wave Equation - da Silva Jr., A. G.; Martins, J. A.; Romao, E. C. (Engineering, Technology & Applied Science Research, 2022)
In this paper, numerical simulations via regressive and central finite differences of different orders were produced using Fortran code and a one-dimensional non-linear wave equation was solved. The errors obtained during simulations, when using different refinements, were listed and compared in order to determine the validity of the simulation, which demonstrates that the proposed formulation presents satisfactory results.